Contrasting Futures for Australia’s Fisheries Stocks Under IPCC RCP8.5 Emissions – A Multi-Ecosystem Model Approach - Pethybridge, Heidi R.; Fulton, Elizabeth A.; Hobday, Alistair J.; Blanchard, Julia; Bulman, Catherine M.; Butler, Ian R.; Cheung, William W. L.; Dutra, Leo X. C.; Gorton, Rebecca; Hutton, Trevor; Matear, Richard; Lozano-Montes, Hector; et al. (Frontiers in Marine Science, 2020)
Climate driven trends in ocean temperature and primary productivity are projected to differ greatly across the globe, likely triggering variable levels of concern for marine biota and ecosystems. Quantifying these changes, and the complex ways in which resource-dependent communities will need to respond, is inherently difficult. Existing uncertainty about the structure, function and responses of marine ecosystems, means that an ensemble model approach is the most robust means of considering potential ecosystem responses to climate change. In this study, climate-ecological projections of 14 marine ecosystem models for regions around Australian were assessed. The models included Ecopath with Ecosim, Atlantis, intermediate complexity, species distribution, and size spectrum models and were all forced by high-resolution ocean forecasting models. Model results found that each Australian region and fishery will face its own challenges in terms of ecosystem shifts and fisheries management responses over the next 40 years. Across assessment regions, demersal systems appear to be more strongly affected by climate change than pelagic systems, with invertebrate species in shallow waters likely to respond first and to a larger degree. With the assistance of qualitative confidence evaluations, the ensemble approach was useful for identifying the likely state of concern for each functional group and thus management priorities. Simulations that considered trophic interactions and feedbacks result in much more realistic responses to climate change, with implications for future assessments and adaption planning. Study results show that fisheries and their management will need to foster pro-active and flexible adaptation options to make the most of coming opportunities and to minimize risks or negative outcomes.